DISTRIBUTING CBM BY USING DENSITY ATRIBUTE FOR DOLPINO BLOCK, SOUTH SUMATRA BASIN, THE PROVINCE OF SOUTH SUMATRA - Nur Hakim, Rizky
Coal bed methane (CBM) is currently one of the producers of unconventional gas that predicted to be the spearhead in the oil and gas industry in Indonesia. The study was conducted to determine the distribution of CBM contained on the Dolpino Block In South Sumatra Basin is known to contain coal in Muaraenim Formation. Research carried out by using the attribute density resulting from the multi attribute training that its spread is limited by facies models. Environment of coal deposition in Muaraenim formation in general is a brackish environment of deposition relative to the direction of northwest - southeast. Cut off the determination of the density obtained from the cross plot between gamma rays and the density of well data from Dolpino-01 and Dolpino-05 with a cut-off value of intermittent density between 1.2 g / cc - 1.65 g / cc and a gamma ray values less than or equal to 50 API. Based on the density attributes distribution from seismic data with density cut off 1.65gr/cc distribution of coal spread randomly and its spread to reach the 50km square area, and based on the results of facies modeling the distribution of coal becomes more restricted and appear spread out more in the zone 3 and zone 4, so in this study that zone become the zone of target for CBM exploration.